Fetal bovine aortic arch – review - Guiljeva, Shehla; Respondek-Liberska, Maria (Prenatal Cardiology, 2021)
Prenatal evaluation of fetal aortic arch is not an easy task, especially during obstetrical screening; however, in tertiary centres, both high-quality ultrasound machines and experience of physicians/echocardiographers have achieved great progress in recent years in the evaluation of this particular part of the fetal heart. It is possible to distinguish between left and right fetal aortic arch, to describe fetal double arch, fetal interrupted aortic arch, coarctation of the aorta, and it is even possible to detect major aorto-pulmonary collateral arteries coming from the descending artery. In a referral centres for fetal cardiology, from time to time we also detect bovine aortic arch, but fetal literature on this topic is rare.